Antimicrobial Efficacy of Alpinia galanga (Linn.) Swartz Flower Extract Against Listeria monocytogenes and Staphylococcus aureus in a Ready-to-Eat Turkey Ham Product - Cadet, M.; Williams , S.K.; Simonne, A.; Sharma, C.S. (International Journal of Poultry Science, 2013)
The pH, objective color and antimicrobial efficacy of Alpinia galanga (Linn.) Swartz Flower Extract (GFE) in a ready-to-eat turkey ham product inoculated with Listeria monocytogenes and Staphylococcus aureus were evaluated. Ham treatments included positive control (inoculated with Listeria monocytogenes and Staphylococcus aureus cocktail only), 0.5% GFE incorporated into meat batter prior to cooking, 1.0% GFE incorporated into meat batter prior to cooking, 0.5% GFE applied to surface of cooked ham after cooled and 1.0% GFE applied to surface of cooked ham after cooled. All samples were inoculated after cooking, then vacuum packaged, stored at 4±1°C for 28 days and analyzed at 1-week intervals. Galangal flower extract exhibited antimicrobial properties and resulted in reductions (p>0.05) of up to 1.00 log cfu/g in S. aureus and L. monocytogenes when compared to the inoculated control. Galangal extract had no adverse effects on objective color and pH.